Implementasi Hukum HAM di Indonesia: Tantangan dan Solusi - Muhammad Maulana Nazril; Dicky Juliandi; Lisda Jumatul Hikmah; Nabela Nabela; Faizah Nazmah; M. Luthfi Setiarno Putera (Perspektif Administrasi Publik dan hukum, 2024)
This article discusses the challenges in the implementation of human rights (HAM) law in Indonesia, despite the existence of a supportive legal framework. The objective of this research is to identify the main obstacles to human rights enforcement and offer solutions to enhance the protection of human rights in the country. The study employs the methods of library research and internet searching to gather data from various academic literature, articles, and relevant digital sources. The research findings indicate that key challenges include a repressive approach to security, a lack of public understanding and awareness about human rights, and legal uncertainty in the enforcement of human rights laws. The conclusion emphasizes the importance of improving human rights education, strengthening law enforcement institutions, and encouraging active public participation in democratic processes as strategic measures to enhance human rights implementation in Indonesia.